Enhancement of hematopoietic recovery in gamma-irradiated mice by the joint use of diclofenac, an inhibitor of prostaglandin production, and glucan, a macrophage activator - Pospísil, M; Hofer, M; Pipalová, I; Viklická, S; Netíková, J; Sandula, J (Experimental hematology, 1992)
The effects of diclofenac (inhibitor of prostaglandin production) and carboxymethylglucan (immunomodulator and an agent stimulating hematopoiesis), when given to mice 1 day before gamma-irradiation, were studied. Both of the agents were administered either alone or in combination. The investigations included the assessment of post-irradiation hematopoietic recovery in terms of bone marrow and spleen cellularity and endogenous spleen colony formation, as well as the determination of the survival of lethally irradiated mice. The results demonstrated at least additive radioprotective effects when mice were given diclofenac and carboxymethylglucan in combination. Experimental evidence provided by the increased 125iodo-deoxyuridine incorporation into the spleen and elevated hydroxyurea kill of endogenous spleen colony-forming units indicated that the beneficial action of the combined treatment could be a consequence of increased cell proliferation in the hematopoietic tissue. It is likely that the inhibition of prostaglandin production (diclofenac action) and the concomitant increased release of growth factors (glucan action) shift the regulatory balance towards the predominance of positive hematopoietic control.
Keywords: záření gama; buněčné dělení; Animals; Gamma Rays; slezina; Whole-Body Irradiation; diklofenak; buňky kostní dřeně; aktivace makrofágů; Bone Marrow; Mice; glukany; Drug Therapy, Combination; Premedication; myši; Hematopoiesis; Glucans; kostní dřeň; Male; Diclofenac; Drug Synergism; Radiation-Protective Agents; Macrophage Activation; Bone Marrow Cells; Spleen; kombinovaná farmakoterapie; synergismus léků; radioprotektivní látky; hematopoéza; zvířata; mužské pohlaví; Cell Division; premedikace; celotělové ozáření